Hyperfractionation as an altered fractionation regimen in primary radiotherapy for squamous cell carcinoma of the larynx - Krstevska, Valentina; Smichkoska, Snezhana (My University, 2006)
The aim of the study was to investigate the efficacy of hyperfractionation as an altered fractionation treatment schedule in comparison with conventional fractionation in primary definitive radiotherapy for laryngeal squamous cell carcinoma. From March 1999 to December 2000, a group of 28 patients with previously untreated squamous cell carcinoma of the larynx were irradiated with conventional fractionation to total doses of 66 to 70 Gy in 33 to 35 fractions/6.5 to 7 weeks, 2 Gy/fraction/day, 5 days/week. From January 2001 to June 2004, the other 27 patients with the same diagnosis, were treated prospectively with hyperfractionation receiving radiotherapy delivered at 1.2 Gy/fraction, twice daily, 5 days/week to 74.4 to 79.2 Gy/62 to 66 fractions/6.2 to 7 weeks. Complete response rates after two months of radiotherapy completion were 78.6% (22 of 28) and 66.7% (18 of 27) in the conventional fractionation and hyperfractionation group, respectively (Fisher exact test; P=0.246). The two year loco-regional control rates were 61.0% +/- 18.1 (95% CI) in the conventional fractionation group and 45.0% +/- 18.8 (95% CI) in the hyperfractionation group (log-rank test; P=0.075). Overall survival rate at two years was 71.0% +/- 16.8 (95% CI) for the conventional fractionation group and 43.0% +/- 18.7 (95% CI) for the hyperfractionation group (log-rank test; P=0.071). The absence of statistically significant differences either in loco-regional control or overall survival observed between the two treatment modalities suggested that hyperfractionation regimen was not more efficacious than conventionally fractionated radiotherapy for previously untreated carcinoma of the larynx.
Keywords: cancer; head; neck; laryngeal cancer